Exploring Urban Imaginaries in Contemporary English Novels Set in London During the 1990s (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article considers how recent English-language novels set in 1990s London invent “urban imaginaries,” that is symbolic, affecting visions of the city marked by memory, displacement, and socio-political change. Set against the context of post-Thatcherite neoliberalism, increased migrancy and cultural dispersal, these narratives provide an alternative, redemptive version of London as a contested space rather than a sovereign geography of mutiplicity and exclusion. This presentation is part of a larger project to analyze the response of literary discourse to dominant spatial and political orders by investigating the dynamic between narrative structure, encounters with the city, and the formation of subjectivity. Using a qualitative interpretive approach, the research uses techniques of literary, narrative, urban cultural, and postcolonial analysis. Comparative close readings of specific novels through the framework of temporality, spatial dismemberment, genre hybridization, and voice. The novels, it is argued, use broken topography, non-linear time and multi-vocal narration to subvert hegemonic depictions of London. They write personal and collective trauma into urban space, creating a “palimpsestic city” whose history of gentrification, racialized policing and marginalization are in the very bricks and mortar of the city. This book provides a look at how narrative strategies (satire, magical realism, dystopian allegory) convey urban postmodernity's attraction and revulsion.They are, in the end, counter-mappings of the city (they break through sanitized urban myths to show other visions that entangle them in justice and pluralised voices). This article makes the case that literature doesn't only depict truth but also changes it. It is through literary description that famous imaginations, lifeworlds and the city itself betakes on a new face -- this is reality seen otherwise and reality remoulded if not eradicated altogether. Do you understand this point of view?